PENGEMBANGAN BUKU SAKU BERBASIS MIND MAPPING DAN MULTIPLE INTELLIGENCES MATERI JAMUR DI SMA NEGERI 1 SLAWI - Juniati, Etika; Widianti, Tuti (Journal of Biology Education, 2015)
Abstract This study aimed to determine the feasibility and effectiveness of the pocket book based mind mapping and multiple intelligences of fungi material in SMAN 1 Slawi. Based on preliminary observations in mind that needs to be developed as a pocket book supporting student handbook, students learn fungi to overcome difficulties and can develop multiple intelligences of students. The method used Research and Development. In large-scale trials using experimental design True Experimental Design with the type of Post - Test Only Control Group Design. Subjects in this study were students of class X PMIA at SMA Negeri 1 Slawi. Feasibility pocket book based on the results of the validation of 80.37 % with a valid criteria and inter-rater reliability (IRRs) value is good, student responses to the legibility of the pocket books of 87.4 % with very good criteria, the response of students and teachers to use the pocket books of 92.25 % with a very good criteria and 95.65 % with a very good criteria. Classical completeness experimental class < 75 % and based on t test obtained thit = 1.41while ttab = 1.67 then thit < ttab and Ho was accepted, student learning outcomes experimental class was almost the same as the control class so pocketbooks less effective. However, the results of multiple intelligences observations indicated that the use of a pocket book is able to develop students multiple intelligences. Development of a pocket book based mind mapping and multiple intelligences of fungi material worthy and able to develop multiple intelligences but less effectively improve student learning outcomes. Abstrak Penelitian ini bertujuan untuk mengetahui kelayakan dan efektivitas buku saku berbasis mind mapping dan multiple intelligences materi jamur di SMA Negeri 1 Slawi. Berdasarkan observasi awal diketahui bahwa perlu dikembangkan buku saku sebagai penunjang buku pegangan siswa, mengatasi kesulitan siswa mempelajari jamur dan dapat mengembangkan kecerdasan majemuk siswa. Metode penelitian yang digunakan Research and Development. Pada uji coba skala besar menggunakan desain eksperimen True Experimental Design dengan jenis Post-test Only Control Group Design. Subjek dalam penelitian ini adalah siswa kelas X PMIA di SMA Negeri 1 Slawi. Kelayakan buku saku didasarkan pada hasil validasi sebesar 80,37% dengan kriteria valid dan nilai inter-rater reliability (IRR) baik, tanggapan siswa terhadap keterbacaan buku saku sebesar 87,4% dengan kriteria sangat baik, tanggapan siswa dan guru terhadap penggunaan buku saku sebesar 92,25% dengan kriteria sangat baik serta 95,65% dengan kriteria sangat baik. Ketuntasan klasikal kelas eksperimen < 75% dan berdasarkan uji t diperoleh thitung = 1,41 sedangkan ttabel = 1,67 maka thitung< ttabel dan Ho diterima, hasil belajar siswa kelas eksperimen hampir sama dengan kelas kontrol sehingga buku saku kurang efektif. Namun, hasil observasi kecerdasan majemuk menunjukkan bahwa penggunaan buku saku mampu mengembangkan kecerdasan majemuk siswa. Pengembangan buku saku berbasis mind mapping dan multiple intelligences materi jamur layak dan mampu mengembangkan kecerdasan majemuk tetapi kurang efektif meningkatkan hasil belajar siswa. Â  Â  Â